Transcriptome Analysis of Cadmium-Treated Roots in Maize (Zea mays L.) - Yue, Runqing; Lu, Caixia; Qi, Jianshuang; Han, Xiaohua; Yan, Shufeng; Guo, Shulei; Liu, Lu; Fu, Xiaolei; Chen, Nana; Yin, Haiyan; Chi, Haifeng; Tie, Shuanggui (Frontiers in Plant Science, 2016)
Cadmium (Cd) is a heavy metal and is highly toxic to all plant species. However, the underlying molecular mechanism controlling the effects of auxin on the Cd stress response in maize is largely unknown. In this study, the transcriptome produced by maize ‘Zheng 58’ root responses to Cd stress was sequenced using Illumina sequencing technology. In our study, six RNA-seq libraries yielded a total of 244 million clean short reads and 30.37 Gb of sequence data. A total of 6342 differentially expressed genes (DEGs) were grouped into 908 Gene Ontology (GO) categories and 198 Kyoto Encyclopedia of Genes and Genomes terms. GO term enrichment analysis indicated that various auxin signaling pathway-related GO terms were significantly enriched in DEGs. Comparison of the transcript abundances for auxin biosynthesis, transport, and downstream response genes revealed a universal expression response under Cd treatment. Furthermore, our data showed that free indole-3-acetic acid (IAA) levels were significantly reduced; but IAA oxidase activity was up-regulated after Cd treatment in maize roots. The analysis of Cd activity in maize roots under different Cd and auxin conditions confirmed that auxin affected Cd accumulation in maize seedlings. These results will improve our understanding of the complex molecular mechanisms underlying the response to Cd stress in maize roots.